2014
DOI: 10.1007/s00411-014-0536-7
|View full text |Cite
|
Sign up to set email alerts
|

mFISH analysis of chromosome aberrations in workers occupationally exposed to mixed radiation

Abstract: We performed a study on the presence of chromosome aberrations in a cohort of plutonium workers of the Mayak production association (PA) with a mean age of 73.3 ± 7.2 years to see whether by multi-color fluorescence in situ hybridization (mFISH) translocation analysis can discriminate individuals who underwent occupational exposure with internal and/or external exposure to ionizing radiation 40 years ago. All Mayak PA workers were occupationally exposed to chronic internal alpha-radiation due to incorporated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…The biological reason for this long-term survival of such heavily damaged PBLs is unclear. However, similar observations, at varying frequencies, have been reported elsewhere including in plutonium workers [87][88][89][90], thorotrast patients [85,91], veterans of nuclear testing [92], A-bomb survivors [93], astronauts and patients receiving carbon therapy [81]. Interestingly, Hande et al [79] found a significant correlation with estimated plutonium dose to the bone marrow (from ~500mGy) and yield of complex aberrations suggesting quantification could potentially be used for dose reconstruction.…”
Section: Complexity Per Se As An Indicator Of High-let Radiationsupporting
confidence: 65%
“…The biological reason for this long-term survival of such heavily damaged PBLs is unclear. However, similar observations, at varying frequencies, have been reported elsewhere including in plutonium workers [87][88][89][90], thorotrast patients [85,91], veterans of nuclear testing [92], A-bomb survivors [93], astronauts and patients receiving carbon therapy [81]. Interestingly, Hande et al [79] found a significant correlation with estimated plutonium dose to the bone marrow (from ~500mGy) and yield of complex aberrations suggesting quantification could potentially be used for dose reconstruction.…”
Section: Complexity Per Se As An Indicator Of High-let Radiationsupporting
confidence: 65%
“…Support for this comes from the in vitro work on long-term cultures reported here. Nevertheless, stable cells containing multiple aberrations are induced by a-particle radiation, albeit in small numbers, and have been observed in studies of workers exposed to internally deposited plutonium (Tawn et al 1985;Whitehouse et al 1998;Anderson et al 2005;Hande et al 2005;Livingston et al 2006;Tawn et al 2006;Sotnik et al 2014). In the current study, such cells were found in three of the nine men (Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…A number of studies have characterized the chromosome aberrations observed in peripheral blood lymphocytes from nuclear workers exposed to a-particle-emitting internally deposited plutonium and attempted to relate these to the cumulative internal dose to the bone marrow (Brandom et al 1979;Tawn et al 1985;Brandom et al 1990;Whitehouse et al 1998;Hande et al 2003;Mitchell et al 2004;Anderson et al 2005;Hande et al 2005;Tawn and Whitehouse 2005;Livingston et al 2006;Tawn et al 2006;Sotnik et al 2014). The majority have identified translocations as the predominant aberration but, although their frequency is greater than that expected from any associated external low LET c-ray exposure, little has been achieved in terms of using translocation frequency to quantify the response following in vivo a-particle exposure.…”
Section: Introductionmentioning
confidence: 98%
“…Non-targeted approaches such as metabolomics, lipidomics and proteomics have provided promising preliminary results for new biomarkers of exposure to radionuclides, as demonstrated by recent studies of uranium (lowest estimated calculated dose of 0.15 mGy in the kidney), 137 Cs (lowest average cumulated dose of 4mGy) and 90 Sr (lowest average cumulated dose of 1 Gy) contamination in rats [216,217,[265][266][267]. Translocations, complex chromosomal rearrangements and micronuclei in peripheral blood lymphocytes (see above) are also potentially useful to estimate cumulated red bone marrow doses resulting from protracted mixed exposure to internal and external IR following moderate to high doses, although further work is needed for complete validation [12,56,59,60,268]. Gender specific mRNA and miRNA gene expression patterns to internal 239 Pu exposure have been deciphered in former Mayak workers [269,270], which are promising markers of internal alpha-particle exposure and warrant further validation.…”
Section: New Biomarkers Of Exposure To Internal Emittersmentioning
confidence: 99%